PUBLIC AND PUBLICLY GUARANTEED EXTERNAL DEBT, DEBT SERVICING AND INVESTMENT IN EMERGING ECONOMIES - Omosuyi, Oluseyi (Economic Annals, 2024)
The global financial crisis of 2007 gave a major boost to the debt-investment nexus debate given the astronomical growth in external debt and its associated debt servicing burdens, which constrain the fiscal space of many developed and emerging economies. Hence, this study examined the effect of external debt and debt servicing on investment in MINT countries for the period, 1990–2021 using the FMOLS estimation technique. The results show that external debt adversely affects investment in Indonesia but stimulates investment in Türkiye while debt servicing has a catastrophic effect on investment in Indonesia and Türkiye but enhances investment in Nigeria. Overall, the effect of external debt and debt servicing on investment in MINT countries are mixed. Hence, the policymakers in each country need to put measures in place to foster debt sustainability, ensure effective domestic resource mobilisation for investment purposes and promote debt transparency by adopting effective debt management practices.